2014
DOI: 10.1016/j.devcel.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Enabled Negatively Regulates Diaphanous-Driven Actin Dynamics In Vitro and In Vivo

Abstract: Summary Actin regulators facilitate cell migration by controlling cell protrusion architecture and dynamics. As the behavior of individual actin regulators becomes clear, we must address why cells require multiple regulators with similar functions and how they cooperate to create diverse protrusions. We characterized Diaphanous and Enabled as a model, using complementary approaches: cell culture, biophysical analysis, and Drosophila morphogenesis. We found Dia and Ena have distinct biochemical properties that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 62 publications
(58 reference statements)
6
79
1
1
Order By: Relevance
“…The fact that formin inhibition did not affect the F-actin organization and content of the Arpc2−/− cells is surprising given the key role that formins play in compensating for the loss of Arp2/3 complex activity in fission yeast (Burke et al, 2014). However, yeast cells do not have proteins homologous to Ena/VASP and recent data in insect cells indicate that Ena/VASP proteins and formins do not merely substitute for each other functionally, but have a more complex interaction than previously suspected (Bilancia et al, 2014). Our data in mammalian cells indicate that Ena/VASP proteins play a major role in compensating for the loss of Arp2/3 complex when it comes to maintaining overall F-actin levels.…”
Section: Discussionmentioning
confidence: 97%
“…The fact that formin inhibition did not affect the F-actin organization and content of the Arpc2−/− cells is surprising given the key role that formins play in compensating for the loss of Arp2/3 complex activity in fission yeast (Burke et al, 2014). However, yeast cells do not have proteins homologous to Ena/VASP and recent data in insect cells indicate that Ena/VASP proteins and formins do not merely substitute for each other functionally, but have a more complex interaction than previously suspected (Bilancia et al, 2014). Our data in mammalian cells indicate that Ena/VASP proteins play a major role in compensating for the loss of Arp2/3 complex when it comes to maintaining overall F-actin levels.…”
Section: Discussionmentioning
confidence: 97%
“…, 2007). Dia, a member of the formin family, is both an actin nucleation and elongation factor (Goode and Eck, 2007; Bilancia et al. , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While a handful of studies have implicated some formins (particularly those of the Dia subgroup) in mediating migration [55,56], the exact mechanisms by which they do so are not completely clear, even in 2D migration. One in vitro study has proposed a mechanism where formins associate with the free barbed ends of filaments nucleated by Arp2/3 to create some of the longer filaments seen at the leading edge of migrating cells [57]; and later work found that the formin Dia and Enabled (a member Ena/VASP family of actin assembly factors) directly interact to modulate the migration speed of Drosophila hematocytes [58]. It will thus be important to address how different mechanisms of actin assembly (e.g., WRC-, WASP-, and formin-mediated), which produce filament networks with distinct architectures, collaborate to drive cell migration under varying environmental conditions.…”
Section: Is Cell Migration In 3d Qualitatively Different Than In 2d?mentioning
confidence: 99%